Students’ Interest in Learning Arabic through Turjuman Al-Qur’an: Minat Siswa dalam Belajar Bahasa Arab Melalui Turjuman Al-Qur’an - Nur, Zain Ahmad Syamil; Hikmah , Khizanatul (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Arabic holds a central role in Islamic education as the language of the Qur’an and Hadith, yet many students in Indonesia still show low interest in learning it. Specific Background: The Turjuman Al-Qur’an program, introduced by the Ummi Foundation in 2015, seeks to strengthen students’ connection with the Qur’an while improving their Arabic learning experience. Knowledge Gap: Despite its implementation, limited studies have explored how this program shapes students’ learning interest, particularly in elementary school settings. Aims: This study investigates the characteristics of students’ interest in learning Arabic, the underlying causes, and the ways they express such interest. Results: Findings reveal five key characteristics of learning interest: focused attention, good memory retention, enjoyment, satisfaction with outcomes, and active participation. Three main causes emerged: internal motivation, teacher methods, and structured classroom rules. Students expressed their interest verbally, through actions, academic achievements, or both simultaneously. Novelty: Unlike previous studies focusing on comprehension, this research uniquely examines the multidimensional nature of Arabic learning interest in Turjuman Al-Qur’an students. Implications: The results highlight the importance of combining innovative pedagogy, supportive classroom structures, and motivational strategies to foster sustainable Arabic learning interest in young learners. Highlights: Identifies five behavioral indicators of Arabic learning interest. Explores three key causes shaping student motivation. Reveals four distinct ways students express their learning interest. Keywords: Arabic Learning, Student Interest, Turjuman Al-Qur’an, Islamic Education, Motivation